2019
DOI: 10.1093/jamia/ocz166
|View full text |Cite
|
Sign up to set email alerts
|

2018 n2c2 shared task on adverse drug events and medication extraction in electronic health records

Abstract: Objective This article summarizes the preparation, organization, evaluation, and results of Track 2 of the 2018 National NLP Clinical Challenges shared task. Track 2 focused on extraction of adverse drug events (ADEs) from clinical records and evaluated 3 tasks: concept extraction, relation classification, and end-to-end systems. We perform an analysis of the results to identify the state of the art in these tasks, learn from it, and build on it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(162 citation statements)
references
References 22 publications
0
162
0
Order By: Relevance
“…Hence, Medical Information Extraction in the Age of Deep Learning Table 4 Medical Named Entity Recognition: Medication Attributes. Benchmark Datasets: n2c2 [56]; i2b2 2009 [57]; MADE 1.0 [59]; DDI [60].…”
Section: Citationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, Medical Information Extraction in the Age of Deep Learning Table 4 Medical Named Entity Recognition: Medication Attributes. Benchmark Datasets: n2c2 [56]; i2b2 2009 [57]; MADE 1.0 [59]; DDI [60].…”
Section: Citationsmentioning
confidence: 99%
“…The top performers for the medication attribute REX task [62] employed a joint learning approach based on CNN-RNN Medical Information Extraction in the Age of Deep Learning Table 5 Medical Relation Extraction: Medication-Attribute Relations (including ADEs). Benchmark Datasets: n2c2 [56]; MADE 1.0 [59].…”
Section: Medication-attribute Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the clinical natural language processing (NLP) community has organized several open challenges such as the 2010 Informatics for Integrating Biology & the Bedside/Veterans Affairs NLP Challenge [ 26 ], Text Analysis Conference 2017 Adverse Drug Reactions Track [ 27 ], and BioCreative V Chemical Disease Relation task [ 28 ]. Recently, 2 such challenges, Medication and Adverse Drug Events from Electronic Health Records (MADE 1.0) [ 29 ] and the 2018 National NLP Clinical Challenges (n2c2) Shared Task Track 2 [ 30 ], were organized to extract drugs , drug attributes, ADEs , reasons for prescribing drugs, and their relations from clinical notes. The results from these 2 challenges showed that deep learning techniques outperform traditional machine learning techniques for this task, and significant improvement is still required for drug−{ADE, reason} relation extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies employed traditional machine learning techniques [ 31 - 34 ], such as conditional random fields (CRF) [ 35 ] for NER and support vector machines [ 36 ] for relation classification. Several recent approaches [ 37 - 44 ], developed on MADE 1.0 [ 29 ] and 2018 n2c2 Shared Task Track 2 [ 30 ] data sets, employed deep learning techniques, such as bidirectional, long short-term memory–conditional random fields (BiLSTM-CRFs) [ 45 ], for NER and convolutional neural network (CNN) [ 46 ] for relation classification, and showed numerous advantages resulting in better performance and less feature engineering. However, there is an inevitable error propagation issue with pipeline-based methods because of the following:…”
Section: Introductionmentioning
confidence: 99%